The Center of Biological Nitrogen Fixation: FeMo‐Cofactor. Issue 1 (5th August 2014) - Spatzal, Thomas
Abstract The enzyme nitrogenase is the only known biological system capable of reducing atmospheric dinitrogen to ammonia, and is therefore an essential player in the biological nitrogen cycle. Despite decades of research, essential questions about the mechanism of nitrogen fixation are unanswered. The complexity of the nitrogenase active site FeMo‐cofactor contributes thereby significantly to the problems nitrogenase research is facing today. Attempts to mimic its exceptional catalytic properties were without success and also the metal center itself exposed only a small fraction of its secrets so far. Today, the FeMo‐cofactor is still the largest and most complex metal center known in biological systems. Solely its structure determination turned out to be an unexpected long process facing multiple hurdles. Even though X‐ray crystallography led to first structural data of the [7Fe:9S:C:Mo]:R‐homocitrate entity more than twenty years ago, only recently the entire atomic structure of the metal center was revealed. This review gives a short overview of the FeMo‐cofactor with a special focus on its structure determination.